Critical thinking in religious education: developing a framework for inquiry-based learning in secondary schools - Ali Reza; Leila Mahdavi; Reza Karimi (Journal Neosantara Hybrid Learning, 2024)
The increasing complexity of contemporary social and religious issues demands a reformation in how religious education is delivered in secondary schools. Traditional approaches often emphasize rote memorization and doctrinal instruction, limiting students’ capacity for independent thought and engagement with pluralistic perspectives. This study aims to develop a pedagogical framework that integrates critical thinking into religious education through an inquiry-based learning (IBL) approach. Employing a qualitative design, the research was conducted in three secondary schools using classroom observations, semi-structured interviews with teachers and students, and document analysis. The findings reveal that incorporating IBL strategies fosters greater student autonomy, promotes respectful dialogue on diverse beliefs, and enhances cognitive engagement. Teachers reported increased student participation and a deeper understanding of ethical and spiritual concepts when lessons were structured around open-ended questions and real-life dilemmas. The study concludes that a well-structured IBL framework can effectively nurture critical thinking within religious education, making it more relevant and transformative for today's learners. It recommends integrating training modules for educators and adapting curricula to include inquiry-driven content.